Carbonyl Activation in Electrophilic Polyene Cyclizations: A Toolbox for the Design of Isoprenoid Libraries. (5th June 2017) - Minassi, Alberto; Pollastro, Federica; Chianese, Giuseppina; Caprioglio, Diego; Taglialatela‐Scafati, Orazio; Appendino, Giovanni
Abstract: An approach to biogenetically overlooked areas of the isoprenoid chemical space is presented. This strategy is based on the generation of a cationic center in functionalized polyolefins by Lewis acid activation of a carbonyl group, rather than by electrophilic attack at a double bond. Starting from the monocyclic humulane trienone zerumbone, polycyclic sesquiterpenoid skeletons which are either not reported as natural products or biogenetically enigmatic in terms of the isoprenoid rule, were obtained by modulating the Lewis acid catalyst. In the course of these studies, the surprising formation of a strained E ‐cyclooctene motif was observed in a cyclization reaction.